La inclusión educativa de alumnos con discapacidades graves y permanentes en la Unión Europea. [Educational inclusion of students with severe and permanent disabilities in the European Union] - López-Torrijo, Manuel (Asociación Interuniversitaria de Investigación Pedagógía, 2009)
This article presents a comparative study of the care of students with severe and permanent educational needs in the six EU countries with greater rates of educational inclusion, (Italy, Greece, Portugal, Norway, Cyprus and Iceland). Such study has been done bearing in mind the following indicators: Analysis of educational needs, identification of deficit, schooling of students in Specific Centres for Special Education, legislative frame, responsibility for schooling and rendering of services, frame and models of schooling, state and functions of Specific Centres of Special Education, curricula of the inclusion, Human resources, family role and funding. From the aforementioned lines are deduced the trends in policies and educational practices carried out are followed. Conclude the necessary changes for the improvement of the future educational educational inclusion. Este artículo presenta un estudio comparado de la atención realizada a los alumnos con discapacidades graves y permanentes en los seis países de la UE que presentan mayores índices de inclusión educativa (Italia, Grecia, Portugal, Noruega, Chipre e Islandia). Dicho estudio está realizado teniendo en cuenta los siguientes indicadores: concepción de las necesidades educativas especiales, identificación de los déficit, alumnado escolarizado en Centros Específicos de Educación Especial, marco legislativo, responsabilidad de escolarización y prestación de servicios, modelo y modalidades de escolarización, estado y funciones de los Centros Específicos de Educación Especial, currículo de la inclusión, recursos humanos, papel de las familias y financiación. De ahí se deducen las tendencias en las políticas y las prácticas educativas realizadas y se concluyen los cambios necesarios para mejorar la inclusión educativa en un futuro.